Changes in ethical competencies among undergraduate counselling students in Malaysia - Zakaria, Ezalinda; Zakaria, Noor Syamilah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
The Counselling Ethics Audit (CEA) is an instrument originally designed to measure ethical knowledge learning outcomes among practicing counsellors in the United States of America. Even though ethics education is required for counselling students, changes in their ethical competencies are not often measured. This research will measure changes in ethical competencies among undergraduate counselling students in Malaysia from participation in an introductory, stand-alone counselling ethics education class. The findings from this research hopefully can provide insights into what topics undergraduate counselling students’ report what they learn in counselling ethics education course and where competency gaps may exist.